Combating corruption in public procurement in developing countries : a legal analysis - Mugadza, W. T. (North-West University, 2018)
This study was motivated by the quest to find new innovative and practical ways of combating public procurement corruption in developing countries to complement the existing measures. This was achieved by comparing three jurisdictions, Hong Kong-China, Botswana and South Africa. The focus was on how each jurisdiction uses the following four measures to curb public procurement corruption: criminal measures; administrative measures; institutional measures and civil activism measures. It was established that Hong Kong uses what this study has classified as the traditional approach of combating public procurement corruption. The traditional approach is characterised by the use of a separate procurement legal framework and a separate corruption legal framework to curb public procurement corruption. Its strengths are in the strict enforcement of criminal measures that are anchored on a robust legal framework, a clear anti-corruption strategy, an independent anti-corruption agency (institutional measure), effective internal oversight and a strong political will. However, the following weaknesses of the traditional approach were identified: over reliance on criminal measures; excessive dependence on one enforcement institution; it neglects the development of administrative measures and has weak civil activism measures. It was established that Botswana uses what this study has classified as the classical approach of combating public procurement corruption. The classical approach is characterised by a procurement legal framework that incorporates very minimum anti-corruption provisions. The anti-corruption provisions in the procurement legislation are enforced by an external institution (the DCEC in the case of Botswana) which relies heavily on the criminal measures. Its strengths are the following: a strong legal framework which provides for a clear anti-corruption strategy; it has anti-corruption units in each Ministry and it has a dedicated Corruption Court. However, the classical approach has the following weaknesses: the anti-corruption agency is not adequately independent as it under the control of the executive (the President in the case of Botswana); lacks effective internal oversight mechanisms; weak political will; neglects the development of administrative measures and civil activism measures are almost non-existent save for the media. It was established that South Africa uses what this study has classified as the traditional cum silo approach of combating public procurement corruption. The traditional cum approach is characterised by multiple procurement legislation which has certain but minimum anti-corruption provisions and a separate corruption legal framework. Multiple anti-corruption agencies are prone to political interference which renders them ineffective and unfit for purpose. Its strength is in the promotion and protection of civil activism measures (right to access information, right to freedom of speech and legal protection of whistle-blowers). Notable weaknesses of the traditional cum silo approach are: the poor enforcement of criminal measures; there is no lead anti-corruption agency that spearheads and coordinates all cases of public procurement corruption; there is no clear anti-corruption strategy; the administrative measures such as debarment are poorly enforced; it has multiple anti-corruption institutions that lack focus and professionalism which results in political manipulation. The thesis concluded by suggesting a new approach, the contemporary approach to combating public procurement corruption which entails the enactment of a single procurement legislation (model law) the Public Procurement and Combating of Public Procurement Corruption Act (hereafter PPCPPC). The contemporary approach advocates for the regulation of public procurement and the combating of public procurement corruption in one legislation. This legislation (PPCPPC) takes into account, the current demands for public procurement as well as future developments of public procurement. These include but are not limited to self-cleaning, cyber-crime and public procurement corruption as well as the role of foreign convictions for debarment purposes. The envisaged PPCPPC will in addition to regulating public procurement, encompass the best criminal measures, administrative measures, institutional measures and civil activism measures. In addition, the contemporary approach through the PPCPPC proposes two new innovations: the corruption clearance certificate and a mandatory anti-corruption clause in all government contracts.
Keywords: Accountability; Administrative measures; Anti-corruption clause; Botswana; Civil activism measures; Classical approach; Combating corruption; Competitiveness; Contemporary approach; Corruption clearance; Criminal measures; Debarment; Equality; Fairness; Hong Kong; Institutional measures; Integrity; Procurement principles; Public procurement; South Africa; Traditional approach; Transparency; Value for money

A South African perspective on the meaning of "beneficial ownership" in Article 10 of the OECD Model Tax Convention on Income and Capital in the context of conduit company treaty shopping - Jansen van Rensburg, Enelia Cornelia (University of Pretoria, 2018)
The use of conduit company treaty shopping structures is often regarded as an impermissible erosion of a country’s tax base. For a developing country, such as South Africa, the protection of its tax base is an important policy consideration. Arguably, one way of combatting conduit company treaty shopping structures is by including in a country’s double taxation agreements the beneficial ownership requirement set out in Article 10(2) of the OECD MTC. The study examines how a South African court would interpret this requirement in provisions in South African double taxation agreements in the context of conduit company treaty shopping involving conduit companies receiving dividends. The study firstly considers whether the beneficial ownership requirement can be regarded as an anti-avoidance rule aimed at combatting conduit company treaty shopping falling outside agents and nominee scenarios. It further considers whether the term “beneficial owner” should have a legal or economic meaning. It explores the meanings given to this term by scholars and foreign courts and the OECD in its Commentaries to the OECD MTC. The study also considers the application of the rules of interpretation contained in the Vienna Convention on the Law of Treaties when giving meaning to this term. Lastly, the study considers whether the term should have the meaning assigned to it under the domestic law of a treaty country, or under international tax law. As part of this enquiry, the meanings of the expression “beneficial owner” in South African case law and legislation are explored.
Keywords: Beneficial ownership; Conduit company treaty shopping; OECD; OECD Model Tax Convention; Société écran; South Africa